Disruptions as Opportunities Governing Chinese Society with Interactive Authoritarianism - Sun, Taiyi (China Understandings Today, 2023)
Disruptions as Opportunities: Governing Chinese Society with Interactive Authoritarianism addresses the long-standing puzzle of why China outlived other one-party authoritarian regimes with particular attention to how the state manages an emerging civil society. Drawing upon over 1,200 survey responses conducted in 126 villages in the Sichuan province, as well as 70 interviews conducted with Civil Society Organization (CSO) leaders and government officials, participant observation, and online research, the book proposes a new theory of interactive authoritarianism to explain how an adaptive authoritarian state manages nascent civil society. Sun argues that when new phenomena and forces are introduced into Chinese society, the Chinese state adopts a three-stage interactive approach toward societal actors: toleration, differentiation, and legalization without institutionalization. Sun looks to three disruptions-earthquakes, internet censorship, and social-media-based guerilla resistance to the ride-sharing industry-to test his theory about the three-stage interactive authoritarian approach and argues that the Chinese government evolves and consolidates its power in moments of crisis.